If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3x + -8) = 2 Reorder the terms: -4(-8 + 3x) = 2 (-8 * -4 + 3x * -4) = 2 (32 + -12x) = 2 Solving 32 + -12x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -12x = 2 + -32 Combine like terms: 32 + -32 = 0 0 + -12x = 2 + -32 -12x = 2 + -32 Combine like terms: 2 + -32 = -30 -12x = -30 Divide each side by '-12'. x = 2.5 Simplifying x = 2.5
| -3-5s=-7-6s | | x+x(.15)=315000 | | -6y+2=4-6y | | f(x)=5x^2-6x+5 | | A=pir^2+2pirh | | X^4-40X^2-33=0 | | 4(3n+1)=6(2n-1) | | 9j=-7+10j | | 24.3=12.4+2a | | -3x-2+1=-7 | | -7g=-2-6g | | 12x^2-16x-6=0 | | -7g=-2-6 | | 12k=-36 | | 16-20x-21-6x=18-6x-12x-1 | | -5y+10=-6y | | 23a+7= | | 9v=10v+9 | | 17-6x+3x-5=x+11+4x | | -3m+10=-4m | | 17-6x+3x-5=x+11 | | 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 | | 10p^2-90p=0 | | x-75x=6x |